Impact of emotional intelligence on the job performance of employee - Pant, Ishita; Yadav, Rakesh Kumar (International research journal of management, IT and social sciences, 2016)
Emotional intelligence means understanding one’s own feelings and able to handle those feelings without disturbing themselves. In the same way, understanding what others feel and handling relationship effectively motivates one to complete job creatively and perform among their peers. Stress Management is a system that is aimed to reduce the stress and/or facilitate the person to cope with stress related instances. This study uses both primary and secondary data. The primary data was collected through a questionnaire which is depending on the Liker scale. The study confined to the sample size of 100 employees from five software industries namely HP, LENOVO, DELL, HCL & SONY, etc. Finally, the researcher finds the relationship between stress management and emotional intelligence. The study is concluded with the suggestion that the Emotional intelligence has the ability to quickly reduce stress in the various situations, so we can say that higher level of EI is positively correlated with the effectiveness of stress management among software employees.